Female Divinities and Story-Telling in the Work of Tamara Kamenszain - Naomi Lindstrom (Studies in 20th & 21st Century Literature, 1996)
Tamara Kamenszain (b. Argentina, 1947), in her creative writing and her essays, brings together two concerns. One is her examination of concepts of woman and femininity. She specializes in mythical and archetypal representations of woman. Her texts present such figures as the great mother and forest nymphs. On many occasions, she evokes a past in which female divinities were respected, even in the Judaic tradition that is frequently Kamenszain's frame of reference. The other current that stands out in Kamenszain's writing is her interest in Jewish traditions of informal narrative. In her texts, folk narrative displaces learned and canonical narrative. Her concern is not only with stories about magic, but also with tale-telling as a magic practice. Kamenszain's writing often makes the point that magic, and particularly feminine magic, has succumbed to modernization. Setting her own writing in opposition to this tendency, Kamenszain brings back feminine magic forces and endows biblical heroines with the talents of sorceresses, priestesses, or goddesses. Her narratives also suggest that women have a special way of reading, learning, and storytelling.
Keywords: Tamara Kamenszain; Argenine literature; creative writing; women; femininity; myth; archetype; great mother; female divinities; Judaic tradition; Jewish tradition; folk narrative; magic; tale; feminine magic